Growth and yield performance of pleurotus ostreatus on various agro-industrial wastes in Malaysia - Fathie, Ahmad Zakil; Mohd Shafiq, Mohd Sueb; Ruzinah, Isha (AIP Publishing, 2019)
The utilization of low value agro-industrial waste as valuable end product has become a key research priority in the recent years. Currently, the commercial cultivation of Pleurotus ostreatus using sawdust from rubber tree as the base substrate in Malaysia has been reported. However, the price and demand of the rubber tree sawdust (RS) have been increasing, affecting the overall production cost. Thus, a new inexpensive alternative substrate yet as effective as rubber tree sawdust is needed to replace the RS as the base substrate for the cultivation of P. ostreatus. In this study, the investigation on substrates from various agro-industrial waste in Malaysia was carried out. Nine different substrates were prepared in combinations in the ratio of 0.25 w/w and 0.5 w/w with empty fruit bunch (EFB), palm pressed fibre (PPF), sugarcane bagasse (SGB) and RS as an alternative substrate for the cultivation of P. ostreatus. These substrates were supplemented with fixed ratio of wheat bran and calcium carbonate to increase the yield of P. ostreatus. The number of days mycelium growth, yield (g/kg substrates), BE (%) and nutrient compositions were studied for different the nine combinations of EFB, PPF and SGB to RS. The substrate of 25%PPF + 25%SGB + 50%RS was found as the best formulation in term of growth performance, yield and biological efficiency (BE) (%) with 35 days for first harvest at 318.88 g/kg and 79.72%, respectively. Thus, the combination of EFB, PPF and SGB demonstrated a great potential as an alternative substrate for the cultivation of P. ostreatus when incorporated with RS.